What can Girlhood Studies be?. Issue 2 (1st June 2021) - Mitchell, Claudia
Abstract : This Special Issue of Girlhood Studies: An Interdisciplinary Journal represents another milestone in the history of the journal, coming, as it does, out of the second international conference of the International Girls' Studies Association (IGSA) that was hosted by Notre Dame University, South Bend, Indiana, in 2019. As the guest editors, Angeletta Gourdine, Mary Celeste Kearney, and Shauna Pomerantz highlight in their introduction, the conference itself and the Special Issue set in motion the type of dialogue and conversation that is crucial to challenging and changing the world of inequities and disparities experienced by girls. For a relatively new area of study that has roots in feminism and social change, critical dialogue about inclusion and exclusion and about ongoing reflexivity and questioning must surely be at the heart of girls studies. The guest editors capture this admirably when they replace the question "What is girlhood studies?" with the provocative and generative question, "What can girlhood studies be?" The articles and book reviews in this Special Issue tackle what girls studies could be in so many different ways, ranging from broadening and deepening notions of intersectionality and interdisciplinarity to ensuring a place for the article, "Where are all the Girls and Indigenous People at IGSA@ND?" co-authored by the girls who belong to the Young Indigenous Women's Utopia group. Such an account offers a meta-analysis of the field of girlhood studies, but so did the call for the Special Issue as a whole. It is commendable that this team of co-editors assembled and curated a series of articles that reveal the very essence of the problematic that girlhood studies seeks to address.